Wear of parts in mechanical engineering. Experimental Analysis of Wear in Spindle Hook Teeth of Cotton Pickers - Temirbay Nurym (Reviews of Modern Science, 2024)
Wear of parts in mechanical engineering is a complex process and has many factors that significantly affect the reliability, durability, and performance of machines and mechanisms. The article discusses the main types of wear, including abrasive, adhesive, corrosion fatigue and erosive wear, and analyzes the factors affecting the speed and intensity of their development. Special attention is paid to materials, loads, lubricants and operating conditions, which determine the degree of wear of parts of mechanisms and machines In addition, modern methods of reducing wear are discussed, such as the use of wear-resistant materials, high-quality lubricants, surface hardening and optimization of structures. An important part of the study is the analysis of diagnostic and preventive methods that allow timely detection of signs of wear and prevent equipment breakdowns. The use of these approaches can significantly extend the period of performance of parts